Business intelligence and the cloud : strategic implementation guide - Gendron, Michael S., 1957- (Hoboken, New Jersey : Wiley, 2014)
How to measure cloud computing options and benefits to impact business intelligence infrastructure This book is a guide for managers and others involved in using cloud computing to create business value. It starts with a discussion of the media hype around cloud computing and attempt to pull together what industry experts are saying in order to create a unified definition. Once this foundation is created-assisting the reader's understanding of what cloud computing is-the discussion moves to getting business benefits from cloud computing. Lastly, the discussion focuses on examples of cloud computing, public clouds, private clouds, and virtualization.
High Variety.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; Cloud computing; Business intelligence; Business; Information technology -- Management; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business intelligence; Cloud computing; Information technology -- Management; Electronic books